Analysis of Wheel Wear and Wheel-Rail Dynamic Characteristics of High-Speed Trains under Braking Conditions - Rui Song; Chenxu Lu; Lixia Sun; Zhongkai Zhang; Dilai Chen; Gang Shen (Shock and Vibration)
When high-speed trains operate under braking conditions, the wheel-rail interaction increases significantly, which can lead to more serious wear problems. To analyze the evolution of wheel wear and the dynamic characteristics of wheel-rail under braking conditions, this paper first carries out long-term monitoring of the service state of wheel-rail during the operation period. The study analyzed the matching characteristics of the measured wheel-rail profile and calibrated the wear model by using the collected data. The resulting wear prediction model was then used to examine the wheel wear characteristics under braking conditions. The research results indicate that during the operation period, the wheel experiences tread concave wear within a range of ±20 mm of the rolling circle, at a rate of approximately 0.05 mm per 10,000 km. Meanwhile, the rail experiences top surface wear at a natural rate of about 0.09 mm per year. Concave wear causes the contact point of the wheel-rail to appear in two zones, resulting in a sudden change of contact geometric parameters. The concave worn wheel and rail with a 60 N profile have better matching compared to the 60 rail profile. Increasing the braking torque and wheel-rail friction coefficient will significantly increase the wheel wear depth on straight sections. On small-radius curve sections, rail side lubrication can significantly reduce high rail side wheel flange wear. A worn concave wheel can lead to unfavorable wheel-rail contact geometry characteristics and increase low-frequency components in the vehicle’s lateral dynamic response.